STUDI FARMAKOVIGILANS PADA OBAT HERBAL - Cantika Nurul Sa'adah (Jurnal Penelitian Farmasi & Herbal, 2022)
There is a trend of "back to nature" which has become the lifestyle of today's society, so that people return to using various natural ingredients in medicine. A drug side effect is any adverse and unwanted response to a drug that occurs at doses normally used in humans for the treatment of disease, diagnosis, prevention, or modification of physiological function. Pharmacovigilance is carried out with the aim of monitoring drug safety by detecting an increase in the incidence of Advers Drugs Reaction (ADR). This review was conducted to see an overview of the initial data/reports on the relationship between the use of herbal medicines and the incidence of ADR. As a result, it is known that the percentage of ADR events in various places is 19%, 12%, 13.36% and 10-15% with possible and probable categories. The types of herbal medicines used are white turmeric, fitsea, garcia, ginger water, turmeric, herbalife, niran, calcusol, vegeta, tensigard, diapet, herbal vegeta, diabetes herbs, hypertension herbs, cholesterol herbs, kidney stone herbs, anti-inflammatory analgesic herbs, herbal medicine for asthma and herbal medicine for diarrhea.